2021
DOI: 10.1111/1753-6405.13135
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors leading to COVID‐19 cases in a Sydney restaurant

Abstract: Objective : To explore the factors associated with the transmission of SARS‐CoV‐2 to patrons of a restaurant. Methods : A retrospective cohort design was undertaken, with spatial examination and genomic sequencing of cases. The cohort included all patrons who attended the restaurant on Saturday 25 July 2020. A case was identified as a person who tested positive to a validated specific Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2) nucleic acid test. Associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Furthermore, an oral transmission route for SARS-CoV-2 was suggested in an outbreak report from Thailand, where individual members of a group fell ill only after sharing a cup with a SARS-CoV-2-infected individual ( Mungmungpuntipantip and Wiwanitkit, 2020 ). Contradictory, other studies found no evidence of SARS-CoV-2 transmission via surfaces or drinking glasses in restaurant settings ( Capon et al, 2021 ; Zhang et al, 2021 ). Syrian hamster model studies have shown, that oral administration of high amounts (10 5 infectious particles) of SARS-CoV-2 resulted in no clinical signs of disease, while intranasal inoculation resulted in ruffled fur, labored breathing, and loss of body weight.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, an oral transmission route for SARS-CoV-2 was suggested in an outbreak report from Thailand, where individual members of a group fell ill only after sharing a cup with a SARS-CoV-2-infected individual ( Mungmungpuntipantip and Wiwanitkit, 2020 ). Contradictory, other studies found no evidence of SARS-CoV-2 transmission via surfaces or drinking glasses in restaurant settings ( Capon et al, 2021 ; Zhang et al, 2021 ). Syrian hamster model studies have shown, that oral administration of high amounts (10 5 infectious particles) of SARS-CoV-2 resulted in no clinical signs of disease, while intranasal inoculation resulted in ruffled fur, labored breathing, and loss of body weight.…”
Section: Introductionmentioning
confidence: 95%